ANALYSIS OF THE EFFECT OF HUMAN RESOURCE COMPETENCY AND DIGITAL INFORMATION ACCESS ON CORN FARMING INCOME IN MONTONG DISTRICT, TUBAN REGENCY - Cipnal Muchlip M; Husain Abdur Rozak; Frestina Bhakti Herwidyaningtyas (Ikatan Dosen Menulis, 2026)
This study aims to analyze the partial and simultaneous influence of education, farming experience, training and extension services, managerial skills, and access to digital information on corn farming income in Montong District, Tuban Regency, and to identify the variables with the most dominant influence. The study employed a quantitative approach with a survey method. The research location was purposively selected in Montong District, Tuban Regency, as one of the corn production centers. The study population consisted of 947 corn farmers belonging to four farmer groups. The sample was determined using the Slovin formula with a 10% margin of error, resulting in 91 respondents selected using proportional random sampling. Data analysis was performed using multiple linear regression with SPSS software through validity tests, reliability tests, classical assumption tests, t-tests, F-tests, and coefficients of determination. The results showed that partially, education and farming experience did not significantly influence corn farming income. Training and extension services had a positive effect, but were not yet significant at the 95% confidence level. Meanwhile, managerial skills and access to digital information had a positive and significant impact on corn farming income. Simultaneously, all independent variables significantly influenced corn farming income. Based on the Standardized Coefficients (Beta) values ​​for the main study variables, managerial skills were the most dominant variable influencing corn farming income. These findings indicate that improving farmers' abilities in planning, organizing, managing resources, and utilizing digital information contributesto to increased corn farming income.